2008
DOI: 10.12693/aphyspola.113.863
|View full text |Cite
|
Sign up to set email alerts
|

Linear Polarized Terahertz Emission under Electrical Breakdown of a Shallow Acceptor in Uniaxially Deformed Germanium

Abstract: We report on polarization spectra of spontaneous terahertz electroluminescence from uniaxially deformed Ge(Ga). At compressive pressure of about 3 ± 0.3 kbar in the [111] direction, near the impurity breakdown threshold, the linear polarization degree attains ≈ 80-90% for the main lines of the terahertz emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Recently, research on shallow impurities in semiconductors has regained considerable interest, because the system is a promising candidate for a simple and coherent terahertz radiation source [3]. It has been demonstrated that the terahertz radiation can be generated from group-III acceptors in Ge in the absence [4] and presence [5][6][7] of stress. Therefore, research on the stress dependence of the oscillator strengths of optical transitions between group-III acceptor states in Ge is an important issue.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research on shallow impurities in semiconductors has regained considerable interest, because the system is a promising candidate for a simple and coherent terahertz radiation source [3]. It has been demonstrated that the terahertz radiation can be generated from group-III acceptors in Ge in the absence [4] and presence [5][6][7] of stress. Therefore, research on the stress dependence of the oscillator strengths of optical transitions between group-III acceptor states in Ge is an important issue.…”
Section: Introductionmentioning
confidence: 99%